Spread OFDM via carrier interferometry spreading codes: performance, throughput, and PAPR enhancement - Wiegandt, David A., author; Nassar, Carl R., advisor; Chandrasekar, V., committee member; Lile, Derek, committee member; Smith, Fred, committee member (Colorado State University. Libraries, 2003)
Orthogonal Frequency Division Multiplexing (OFDM) has been an important technique in wireless communication architectures since the 1970's and 1980's. OFDM is now the protocol in the IEEE 802.11a and IEEE 802.1 lg Wireless Local Area Networks (WLANs) standards, as well as the IEEE 802.16 Fixed Broadband standard. It is also a front-runner for implementation in future cellular standards and satellite systems. However, OFDM is not without its limitations - both in terms of performance and Peak-to-Average Power Ratio (PAPR). In this dissertation, the author significantly enhances the performance of traditional OFDM systems via the introduction of novel Carrier Interferometry (Cl) spreading codes. Specifically, this research demonstrates through computer emulation and RF testing, that the application of Cl spreading codes to OFDM, leads to significant performance gains (relative to traditional OFDM), and an eliminated PAPR issue. The novel OFDM techniques introduced in this dissertation will significantly enhance the abilities of OFDM in the years to come.
Keywords: electrical engineering